Three Sphagnum taxa new to Turkey and South-West Asia - Öznur Özen-Öztürk; Turan Özdemir; Nevzat Batan; Hüseyin Erata (Botanica Serbica, 2023)
Sphagnum jensenii, S. fallax var. isoviitae, and S. pylaesii were found as new to Turkey and Southwest Asia following a bryological field trip to the Giresun province of Turkey. Sphagnum fallax var. isoviitae was also new to Asia. Descriptions, illustrations, world distribution, ecology, and comparisons with related species are presented.